Natural killer cells: the next wave in cancer immunotherapy - Chen, Xin; Jiang, Lei; Liu, Xuesong (Frontiers in Immunology, 2022)
Immunotherapies focusing on rejuvenating T cell activities, like PD-1/PD-L1 and CTLA-4 blockade, have unprecedentedly revolutionized the landscape of cancer treatment. Yet a previously underexplored component of the immune system - natural killer (NK) cell, is coming to the forefront of immunotherapeutic attempts. In this review, we discuss the contributions of NK cells in the success of current immunotherapies, provide an overview of the current preclinical and clinical strategies at harnessing NK cells for cancer treatment, and highlight that NK cell-mediated therapies emerge as a major target in the next wave of cancer immunotherapy.